Vertebrate animals of the forest - Das, Indraneil (Singapore : Sun Tree Pub., 1994)
his is a richly illustrated portrait of a pristine forest on the island of Borneo. It provides a case study for the wise management of a key global environment. The authors draw on their background as educators, with long personal experience of tropical habitats, and have interwoven the specialist contributions of other participants in the Brunei Rainforest Project (1991 -92). Geography and biological disciplines are brought together to describe the unmatchable wealth of wildlife there. Starting from a summary of the equatorial climate, the regional geology, landform processes and soils, the text focuses on the complexity of tropical rainforest biodiversity and ecology. Special sections cover different forms of life and the environments in which they occur. The closing chapters discuss the place of people, and their role in the sustainable management of this immeasureably valuable biodiversity resource